Group B streptococcal meningitis in a healthy young woman: A case report - Alvin Oliver Payus; Clarita Clarence; Raymond Azman Ali (Dove Medical Press Ltd, 2020)
Group B streptococcus (GBS) is a rare cause of meningitis in adults that commonly affects patients with multiple underlying comorbidities. Although it is uncommon, it typically progresses very rapidly and has a high mortality rate as compared to other causes of bacterial meningitis. Here, we report a patient with GBS meningitis who had no underlying medical illness and presented with multiple episodes of seizure within hours of developing fever. Cerebrospinal fluid analysis results were consistent with bacterial meningitis, and blood cultures grew GBS. She was treated with intravenous ceftriaxone for 2 weeks and made a great recovery without any sequalae. In conclusion, although GBS meningitis is uncommon in adults, it is a serious medical disease and associated with a high mortality rate. To the best of our knowledge, this patient represents one of the few reported cases of GBS meningitis in a previously healthy young adult.